Caracterização fotofísica de derivados de Cumarinas - Miranda, Jacques Antonio de (2001)
The photophysics of three coumarins derivatives has different organic solvents, by steady-state and time-resolved fluorescence measurements. These measurements were performed both at room temperature and at 77 K. The high molar absorptivities, approximately 104 mol''dm3cm’1, associated to S()—>Si transition, suggest a k,k* character. This character is principally due to the electron-withdrawing effect of the benzoxazole group iocated at 3-position of the coumarin ríng. An n,%* perturbational contribution can also occur due to the interaction of eletron donor substituents t The results show that the coumarins studied here fluorescent. However. the kind of substituent at 7-positoin of coumarin ring has an important effect on the properties. For the 3-benzoxazoí-2-il-7-diethylamino-cromen-7-one derivative, the combination of the two substituents at positions 3 and 7 can viabilize an intramolecular charge transfer (ICT) at the ground State; effect which íncreases in the first excited singlet State. The excited State observed from fluorescent emission has a TICT character. The behaviour of this compound is affected by soívent polarity, principally protic solvents, where the formation of hydrogen bonds favors the non-radiative deactivation of Si State. This compound nd the deprotonated hydroxylated derivative show a temperature dependence for The pH effect on spectroscopic properties was investigated for aminocoumarin and hidroxycoumarin. In the latter an anionic specie is formed. It shows distinct photophysical properties from the neutral species. A pKa of 6.20 estimated for the acid-base equilibrium. Non-radiative deactivation processes rease when the anionic form predominates, due to the interactions between the ani• oni• c specie a<nuwd its counter ion. A similar behaviour is observed in nucleofilic Jvents Üke DMF and DMSO. The anionic species present an intramolecular harge transfer originating from the ketonic group at 7 position, formed due to the d rotonation In the excited State is still possible to observe a third species at below pHU AO fuhwat i1s3 attributed to the cationic form, formed by the protonation of hidroxyl group. IIIA pKa of 2.36 was estimated for aminocoumarin. The intramolecular charge transfer State is inviabilized after protonation of the amino group, where there is no eletronic coupling with the coumarin ring. The cationic specie at the excited State is strongly deactivated by internai conversion. The 3-benzoxazol-2-iI-cromen-2-one derivative showed a singlete oxygen generation quantum efficiency of 15 %, whereas the others an efficiency of approximately 6 % was found.